Ostatnie chwile mieszkańców Konstantynopola w greckich wernakularnych lamentach o zdobyciu Miasta w 1453 roku - Bzinkowski, Michał (Vox Patrum, 2026)
In my article, based on selected fragments of laments written in vernacular Greek between the 15th and 16th centuries (Ανακάλημα της Κωνσταντινόπολης, Άλωσις Κωνσταντινουπόλεως, Θρήνος της Κωνσταντινουπόλεως), I focus on images of the suffering of the population of Constantinople during its conquest by the Turks in 1453. By juxtaposing passages containing dramatic descriptions of the enslavement and humiliation of the conquered population, I try to show what poetic devices the anonymous poets used to convey the horror of the situation. By quoting the accounts of the last Byzantine historians Doukas and Kritoboulos, I also try to shed some light on the question of the interrelation of post-Byzantine vernacular texts and those written in learned classical Greek. The comparative and linguistic analysis carried out in the article demonstrates not only the mutual dependence between the historians’ accounts and the anonymous laments, but shows that any picture of Byzantium from a Greek perspective without considering the context of vernacular literature is incomplete.